Optimalisasi geostrategi indonesia dalam menghadapi tantangan global dan regional - Humaira, Rana Tsabitah (Maliki Interdisciplinary Journal, 2026)
Indonesia’s geostrategy is a national approach that utilizes its geographical location, natural resources, and socio-political potential to achieve national goals. Amidst the era of globalization and geopolitical dynamics in the Indo-Pacific region, Indonesia faces various challenges, both global and regional, such as major competition, maritime security threats, climate change, the global economics crisis, and advances in digital technology. This research aims to analyze the optimization of Indonesia’s geostrategy in facing these challenges using a qualitative-descriptive approach with a literature study of scientific journals and national policy documents. The results of the study indicate that to optimize Indonesia’s geostrategy, it is necessary to strengthen national resilience, active diplomacy maritime economic development, defense modernization, and strengthening regional cooperation, especially with ASEAN. In addition, the application of the concept of Wawasan Nusantara and national resilience are important foundations in maintaining national sovereignty amid global dynamics. Indonesia also needs to increase technological capacity, human resource development, and domestic political stability to maintain its strategic position in the Indo-Pacific region. With effective geostrategic optimization, Indonesia can increase national competitiveness while maintaining its position at the regional and international levels.